Host morphophysiological conditions and environment abiotic factors correlate with bat flies (Streblidae) prevalence and intensity in Artibeus Leach, 1821 (Phyllostomidae) - Priscilla Maria Peixoto Patrício; Elizabete Captivo Lourenço; Aline Quintanilha de Freitas; Kátia Maria Famadas (Ciência Rural, 2016)
ABSTRACT: The aim of this study was to correlate Streblidae parasitism rates with temperature and humidity as well as sex, age and reproductive condition of Artibeus bats. Streblidae specimens were collected during two years in the Tinguá Biological Reserve and in two areas inside buffer zone, located in Nova Iguaçu, Rio de Janeiro State and preserved as wet specimens. The abundance of Streblidae species parasitizing Artibeus was analyzed, and no differences were found between them. However, the number of females parasitizing Artibeus fimbriatus was higher. Moreover, regarding sex, Artibeus females were more parasitized, particularly A. fimbriatus and A. lituratus. There was no correlation between mean intensity of infestation and body mass index of Artibeus species, even when correlated to abiotic data. This study contributes to better understand the parasitism on Artibeus by Streblidae, and based on results, it is clear that Streblidae show no preferences in terms of reproductive condition, body size, age, sex, temperature and humidity in parasitizing Artibeus species.